Correlation between material properties, grinding effects and Barkhausen noise measurements for two crankshaft steels - Doverbo, Marie (My University, 2012)
The crankshaft steel of two suppliers has been shown to yield differing Barkhausen measurements despite corresponding material specifications and identical manufacturing. In this thesis the reason for this discrepancy is investigated and an hypothesis regarding its cause is formulated. The conclusions are reached through experimental work, wherein the material properties of the two steels are compared. The difference in ductility is related to the difference in Barkhausen Noise Amplitude (BNA) through the grinding process such that the increased ductility is believed to increase the chip build up in the grinding wheel, thus resulting in higher grinding temperature. This would increase the risk for grinding burns and moves the residual stresses towards tensile, which changes the BNA. Suggestions for future work all concern the verification of this hypothesis.
Keywords: Materialteknik; Metallurgi och metalliska material; Materialvetenskap; Produktion; Materials Engineering; Metallurgy and Metallic Materials; Materials Science; Production